Socio-philosophical aspects of the information space of Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
Modern society is characterized as information-oriented, which specify features its socially-philosophical research. The epoch “after modernity” is characterized by an increase in the volume of information flows, the virtualization of communication interaction, resulting in the formation of virtual or network identities. Article is devoted to the analysis and the characteristic of a phenomenon of the virtual communication playing the dominating role in the world of e-culture. The author offers classification of types of virtual communication depending on character of the relations of subjects. Lines and the features inherent in virtual communication are as a result revealed, advantages and risks to the person and society are opened. A problem of subsistence of people under the conditions of modern information-oriented society is considered in the present paper. The article is devoted to some socio-philosophicalissues of the contradictory influence of virtual interaction on a communicative individual. There are analyzedthe social and cultural conditions, in which the Internet originated, revealed the preconditions foronline social networks phenomenon, regarded as the factor for reality virtualization. The influence of theglobal network, Internet, on the material and spiritual culture of man is described in detail. Informationcommunicationtechnologies are considered as a factor of national safety maintenance in conditions ofglobalization. Current risks of information and communication effects on a national state, society andindividual are revealed. As well as the main social and philosophical aspects of virtual communicationpractice in the information space of Kazakhstan.Key words: virtual communication, virtualization, information society